DEIKSIS PADA ENGKANA DALAM MASYARAKAT DAYAK SEBERUANG DESA NANGA PARI KECAMATAN SEPAUK KABUPATEN SINTANG - Lonika, Tessa; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Indonesia has various ethnic groups and languages, one of which is the Dayak language. The Dayak Seberuang oral tradition is a tradition whose stories develop towards the language, culture, and people of the Dayak Seberuang. This study aims to describe and analyze Engkana deixis in the Dayak Seberuang community in Nanga Pari Village, Sepauk District, Sintang Regency. The research method used is descriptive method with a qualitative research form. Techniques in data collection are interview techniques, recording, and notes. Based on the results of data analysis, (1) there are 11 forms of site deixis consisting of 3 distal site deixis, 4 proximal site deixis, and 4 semi-proximal site deixis. (2) there are 16 forms of persona deixis consisting of the first persona deixis singular 2 data, the first persona plural 4 data, the second persona singular 6 data, the second persona plural 1 data, the third persona singular 1 data, the third persona plural 2 data. (3) there are 9 forms of time deixis consisting of 5 deixis of time of past events, 1 deixis of time of present events, and 3 deixis of time of future events. The meaning of deixis in the form of words was analyzed using the lexical meaning and the data in the form of phrases were analyzed using the grammatical meaning. The form of Indonesian language learning e-modules based on fable texts.